Enhancement structure probiotic yoghurt made from whole milk powder by psyllium husk - Darwish, Alzahraa Mohamed (Journal of Food Technology Research, 2023)
Psyllium husk is a bioactive source that provides health benefits and is new best possible use in the dairy industry as a texture enhancer for its hydrochloride properties. The current study focuses on the optimization of a suitable amount of psyllium husk powder (PHP) with whole milk powder (WMP) to produce bioactive probiotic yoghurt and keep it stable during the storage period. The different levels of PHP (0, 0.5, 1.0, and 1.5 % w/w) with WMP were used to prepare the bioactive probiotic yoghurt as a functional food. We made four different mixtures and tested them for their chemical makeup (pH, titratable acidity, moisture, total solids, ash, fat, and protein), colour (L*, a*, b*, and C*), ability to hold water (WHC), and how they tasted after 1, 7, and 14 days at 5°C. The PHP probiotic yoghurt showed a significant decrease (p < 0.05) in pH, protein, and fat. While titratable acidity and ash contents were increased compared with the control. Also, the texture profile, like adhesive and hardiness, had better flow properties and more WHC than the control. Additionally, the color parameter showed an increase in a*, b*, and C* values and a decrease in the L* value. The sensory evaluators preferred the 1% PHP samples. The current study found that samples fortified with 1% PHP improved the physicochemical, texture, and sensory properties of probiotic yoghurt and maintained probiotic yoghurt structure during storage compared with the control. Probiotic yoghurt prepared from PHP has provided new dairy industrial applications.